Systematic Country Diagnostic : Kenya - World Bank (World Bank, Washington, DC, 2020)
This World Bank Systematic Country Diagnostic (SCD) provides an analytical foundation for identifying country-level actions and investments that would increase growth and boost shared prosperity in Kenya. The conceptual framework adopted for this SCD is organized around two main strategies: (1) higher aggregate output and productivity growth and (2) greater equity and inclusiveness.